Indicators of Regulatory Management Systems - Jacobzone, Stephane (OECD Working Papers on Public Governance, 2007)
This report presents detailed results on the quality of regulatory management systems, following the survey conducted in 2005-6. The goal of this report is to compare regulatory quality assurance systems; to measure progress and understand trends over time across countries, and to identify general patterns of regulatory management practice. Following initial discussions over the survey instrument in 2005, they survey was circulated in June 2005 and the results, corresponding to 2005, were then collected with final submissions received in Spring 2006. This paper has been revised following comments received from delegates in the Autumn 2006 and Spring 2007. The current set of results also links to previous regulatory governance indicators collected by the OECD in 1998 and 2000. Some of the early phase issues in terms of checks and a correction of the understanding of the concepts led to a revision of previous 1998 estimates. Therefore, this report is based on the corrected results for 1998 and 2000 received from the countries that had been surveyed then. These results also feed into the OECD Project on "Management in Government" (OECD (2007), "Towards Better Measurement of government", OECD Working Papers on Public Governance, 2007/2, OECD Publishing. Doi:110.1787/301575636734). This paper restricts itself to a descriptive presentation of the materials collected. Further methodological work will be undertaken as this project evolves to conduct more technical statistical analysis and build aggregated indicators. This work benefited from insights and comments from OECD colleagues. The authors are particularly grateful to Rolf Alter, Josef Konvitz, Glen Hepburn and Nick Manning for their comments, as well as to Peter Ladegaard who participated in some of the initial work. The authors are also indebted to Sander Wagner for statistical assistance